Lokales Integrationsmanagement in Deutschland, Schweden und Frankreich Verwaltung und Koordination im Mehrebenensystem - Bogumil, Jörg; Fleischer, Julia; Färber, Gisela; Gerstelberger, Wolfgang; Hammerschmid, Gerhard; Hansmann, Marc; Kuhlmann, Sabine; Meyer, Renate E.; Mezger, Erika; Naschold, Frider; Schaefer, Christina; Schneider, Karsten; et al. (Modernisierung des öffentlichen Sektors ("Gelbe Reihe"), 2023)
This study analyses local integration management in Germany, France and Sweden from a comparative perspective. It focuses on the inter-administrative relations, coordination and performance of integration management, with a particular focus on developments after the refugee crisis of 2015/16. Based on case studies and expert interviews in the aforementioned three countries, it analyses the institutional interplay between actors in both the multi-level system and the local sphere. The authors examine the national contexts, local institutional settings and crisis-related challenges of integration management performance in the three countries, taking similarities and differences from a cross-country and inter-municipal com-parative perspective into account. Using illustrative examples from practice and deriving lessons from in-depth insights into local problem-solving, the study makes recommendations for the optimisation of integration management and more crisis-resilient administrative organisation in this policy area.